Pengaruh Persepsi Harga, Kualitas Produk, dan Lokasi terhadap Keputusan Pembelian: Studi Kasus Kedai Kopi Difabis Sudirman Jakarta - Saputri, Az Zahra; Paludi, Salman (Journal of Economics, Bussiness and Management Issues, 2024)
This study aims to determine the influence of price perceptions, product quality, and location on purchasing decisions at Kedai Kopi Difabis Sudirman Jakarta. The research employs a quantitative method with a sample size of 100 respondents, selected using an accidental sampling technique. Data was collected through a questionnaire distributed via Google Form and analyzed using SPSS software. The analysis was conducted by applying multiple linear regression analysis, as well as correlation and determination coefficients. The results of the research indicate that price perceptions do not have a significant influence on purchasing decisions, whereas product quality and the location of Kedai Kopi Difabis Sudirman Jakarta significantly influence purchasing decisions. The conclusion of this study is that product quality and location are important factors influencing consumer purchasing decisions at Kedai Kopi Difabis Sudirman Jakarta, while price perceptions do not have a significant impact. These findings can be utilized by the management of Kedai Kopi Difabis to focus on enhancing product quality and selecting strategic locations to improve consumer purchasing decisions.